METHYLPREDNISOLONE THERAPY IN ACUTE SPINAL CORD INJURIES - Zagorac, Slaviša (Srpski medicinski časopis Lekarske komore, 2021)
Spinal cord injuries represent a major challenge in terms of current concepts of treatment. This condition is frequently associated with long term therapy in addition to a greater incidence of early and late complications. The goal of treatment is to alleviate pressure on the spinal cord caused by hematomas or bone fragments, in the shortest time possible. Hence, surgical decompression of the spinal cord is the first line of treatment, in cases where this approach is indicated. Apart from invasive methods, treatment also consists of the use of various pharmacological agents, whose therapeutic goal is to decrease edema and inflammation, especially in the first several days following injury. One of the most commonly administered drugs in such cases is methylprednisolone, however, controversy with regards to the timing of its administration and proper dosing, still exists. This drug has been in use for decades in the treatment of spinal cord injuries with various protocols having been introduced and revised overtime. The aim of this article is to showcase the current understanding of the use of corticosteroids in acute spinal cord injuries. The most significant protocols in use today for the administration of methylprednisolone (National Acute Spinal Cord Injury Studies-NASCIS I, II and III), along with a brief overview of pertinent literature, are discussed in this paper. Analysis of the available data suggests that the use of methylprednisolone in spinal cord injuries is still highly controversial due to the inconclusive relationship between the therapeutic benefits and the risk of side effects. The current understanding is that the use of the drug is justified in the first eight hours following injury, especially in cases involving incomplete neurological deficits, more specifically quadriparesis and paraparesis.
Keywords: acute spinal cord injury; methylprednisolone; incomplete neurological deficit